Bahasa Inggris - Sumardi, Fitri Sepviyanti (Jurnal Komplikasi Anestesi, 2025)
Introduction: Thymectomy in patients with myasthenia gravis or mediastinal tumors requires a very careful anesthesia strategy due to neuromuscular sensitivity, risk of airway compression, and possible hemodynamic instability. This systematic literature review summarizes the latest evidence on anesthesia governance, including engineering innovations and their implications for facilities with limited resources.Methodology: Literature searches were conducted through PubMed, Scopus, and Google Scholar using keywords related to "thymectomy", "anesthesia", "mediastinal mass", and "myasthenia gravis". The inclusion criteria include prospective studies, retrospectives, systematic reviews, meta-analyses, and case reports (2019–2025), as well as one 2013 case report. Out of 450 publications, 30 articles met the PRISMA criteria and were analyzed narratively. Results: Comprehensive preoperative evaluation was the main determinant of anesthesia success in patients with neuromuscular and mediastinal mass disorders. Anesthesia techniques without muscle relaxants or with propofol TCI/sevoflurane have been shown to provide better neuromuscular stability. Sugammadex produces a faster and safer reversal than neostigmine. In large mediastinal masses, special strategies such as awake intubation, spontaneous ventilation, double-lumen tube, or ECMO readiness reduce the risk of airway collapse. Minimally invasive techniques (VATS/robotics) show faster recovery and lower complications, especially when combined with advanced respiration monitoring. Discussion & Conclusion: The success of thymectomy anesthesia relies heavily on three pillars: thorough preoperative evaluation, risk-based individualized anesthesia techniques, and rigorous intraoperative monitoring. Innovations such as sugammadex, spontaneous ventilation, and advanced monitoring technology improve safety and speed up recovery. In resource-limited settings, strong clinical skills and teamwork enable effective outcomes with minimal technology.